The Association Between the Physical Fitness Index and the Grade Point Average in Faculty of Medicine UMSU Students - Lubis, Debby Mirani; Asfur, Robitah (Buletin Farmatera, 2021)
The GPA (Grade Point Average) is the passing score for each course a student gets every semester which is currently often used as a requirement for further study students (Masters or Specialists) or applying for jobs so that the GPA is considered important to describe student intelligence during taking the educational process. Many things affect student intelligence, one of which will be discussed and proven in this study is the value of the Physical Fitness Index. This study aims to determine the relationship between the Physical Fitness Index and the GPA score of FK UMSU students. This research is an analytical study using a cross-sectional approach. The research site was conducted at the Faculty of Medicine UMSU from April to June 2020. A total of 94 subjects with male gender totaled 25 people (26.6%), women totaled 69 people (73.4%). Based on the measurement of the Physical Fitness Index which was carried out using the Harvard Step Test method, the mean value of all 2018 students was 49.57. The average GPA of all 2018 students was 3.00. Based on the results of the statistical test, the relationship between the Faculty of Medicine UMSU student body fitness index and the cumulative grade point average is p = 0.87. Therefore, it can be concluded that there is no significant association between the Faculty of Medicine UMSU student body fitness index and the grade point average.